2013
DOI: 10.1136/bmjspcare-2012-000408
|View full text |Cite
|
Sign up to set email alerts
|

Teaching the difficult-to-teach topics

Abstract: It is now accepted that teaching in palliative medicine should be integrated throughout the medical undergraduate curriculum. Recommendations suggest the inclusion of knowledge areas such as symptom control, as well as more attitudinal aspects such as teamwork and understanding patient and carer perspectives on illness. These subjects should be taught on a stepwise basis, introducing concepts at an early stage and then be built on throughout training. However, how this is done and how effectively all aspects a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 11 publications
0
11
0
6
Order By: Relevance
“…For example, knowledge areas such as opioid conversion may be taught in calculation tutorials, whereas attitudinal areas such as truth-telling require theoretical teaching with mentored clinical exposure. 47 , 48 In the setting of minimal protected curricular time and a shortage of palliative care providers, intentional exposure to diverse teaching modalities equips instructors with practical teaching tools and enables learners with an accessible knowledge base ( Table 2 ). The reality of palliative care as a young and an understaffed field has led to the prioritization of educating trainees as palliative care champions to share their knowledge in local settings.…”
Section: Training Interventions: Instructional Strategiesmentioning
confidence: 99%
“…For example, knowledge areas such as opioid conversion may be taught in calculation tutorials, whereas attitudinal areas such as truth-telling require theoretical teaching with mentored clinical exposure. 47 , 48 In the setting of minimal protected curricular time and a shortage of palliative care providers, intentional exposure to diverse teaching modalities equips instructors with practical teaching tools and enables learners with an accessible knowledge base ( Table 2 ). The reality of palliative care as a young and an understaffed field has led to the prioritization of educating trainees as palliative care champions to share their knowledge in local settings.…”
Section: Training Interventions: Instructional Strategiesmentioning
confidence: 99%
“…Segundo MacPherson et al 34 , o ensino deve estar integrado no currículo da graduação, e recomenda-se a inclusão de áreas de conhecimentos como controle de sintomas, trabalho em equipe e cuidado da pessoa desde as etapas básicas do adoecimento.…”
Section: Resultsunclassified
“…All articles indicated improvements in student knowledge, attitudes, and/or preparedness to practice palliative care concepts compared to no intervention. 5,6,19,42 93 Most articles used pretest/posttest surveys or qualitative analysis of student reflections to evaluate the teaching intervention. Only 1 article was identified that evaluated several different teaching methods against a control to assess optimal strategy for teaching regarding cancer pain.…”
Section: Resultsmentioning
confidence: 99%